THE SENSORY EVALUATION ON PUMPKIN ICE CREAM THAT FORMULATED BY RED DRAGON FRUIT - Prayitno, Sutrisno Adi; Rahma, Amalia (Food Science and Technology Journal (Foodscitech), 2019)
The types of fruit that are often used in functional foods are pumpkin and red dragon fruit. Pumpkin contains high levels of beta-carotene and proved to be useful in mobilizing iron reserves in the body in haemoglobin synthesis. On the other hand, the ingredients in dragon fruit is almost the same as pumpkin, which contains iron elements that play a role in the formation of blood, namely in the synthesis of haemoglobin. The existence of pumpkin and red dragon fruit can be processed into functional food. One of the functional food products is ice cream. The purpose of the study was to find out the organoleptic quality of pumpkin ice cream that formulated with red dragon fruit. The sensory evaluation on ice cream was carried out by hedonic test. The proportion of comparisons between pumpkin and dragon fruit used was four treatments. Treatment A is 100% : 0%, treatment B is 80% : 20%, treatment C is 50% : 50% and treatment D is 60% : 40%. In sensory evaluation using untrained panellists. The determination of the best formulation on the product is obtained from the average value of the highest overall acceptability. The hedonic results show that the pumpkin ice cream and dragon fruit formulations are generally accepted (colour, smell, taste and texture) with the category is likes. In terms of colour, texture and smell the most preferred by untrained panellists is in the C formulation (50 %: 50%). In terms of taste, the panellists preferred in D formulation (60%, 40%). By this, it can be concluded that the best formulation that can be recommended is in the C treatment by the proportion of 50 %: 50% pumpkin and red dragon fruit.